2021
DOI: 10.3389/fmicb.2021.606087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Synonymous Genome Recoding on the HIV Life Cycle

Abstract: Synonymous mutations within protein coding regions introduce changes in DNA or messenger (m) RNA, without mutating the encoded proteins. Synonymous recoding of virus genomes has facilitated the identification of previously unknown virus biological features. Moreover, large-scale synonymous recoding of the genome of human immunodeficiency virus type 1 (HIV-1) has elucidated new antiviral mechanisms within the innate immune response, and has improved our knowledge of new functional virus genome structures, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 97 publications
1
11
0
Order By: Relevance
“…Codon pair deoptimization has been widely used to generate attenuated viruses [ 1 , 2 , 14 ], including HIV-1 [ 6 , 9 , 10 ]. We previously demonstrated that codon pair deoptimization of the HIV-1 gag and pol genes strongly compromises virus replication capacity and viability [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Codon pair deoptimization has been widely used to generate attenuated viruses [ 1 , 2 , 14 ], including HIV-1 [ 6 , 9 , 10 ]. We previously demonstrated that codon pair deoptimization of the HIV-1 gag and pol genes strongly compromises virus replication capacity and viability [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 is no exception, with its genome displaying a significantly lower than expected number of CpGs [ 24 ]. Several studies demonstrate that increasing CpG frequencies have negative effects on HIV-1 fitness, as previously reviewed [ 6 ]. HIV-1 env CpG dinucleotide suppression reportedly enables the virus to evade inhibition by ZAP in MT-4 cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the introduction of numerous synonymous mutations throughout the HIV-1 genome, especially into the central region of the genome, results in replication defects via splicing perturbation [ 56 ]. Several lines of evidence showed that synonymous mutations can affect pivotal biological processes such as RNA splicing, RNA stability, and translation efficiency [ 56 , 57 , 58 ], for review, see [ 59 , 60 ]. This implies that synonymous mutations would be biologically relevant and exposed to selective forces.…”
Section: Discussionmentioning
confidence: 99%